Sustainability Disclosure Practices in Islamic Banking: Do Audit Committees Matter for SDG 16? - Rita Wijayanti; Doddy Setiawan; Y. Anni Aryani; Taufiq Arifin (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: To examine the influence of audit committee (AC) characteristics on the level of sustainability disclosure in Islamic Banks (IBs) listed on the Indonesia Stock Exchange during the period 2012–2021. Method: Employing a quantitative approach using purposive sampling to obtain 13 Islamic banks, resulting in 122 unbalanced panel data observations. Secondary data were collected from annual reports available on each bank’s official website. Sustainability disclosure items were adopted from Jan et al. (2019) and measured using content analysis techniques. The hypotheses were tested using panel data regression with the random effects model. Results: The findings indicate that Islamic banks disclosed only approximately 27% of the sustainability information expected. Furthermore, the number of audit committee members and audit committee independence significantly influenced sustainability disclosure practices, suggesting that effective oversight mechanisms encourage greater transparency regarding sustainability performance. Novelty: Extending the literature on sustainability disclosure by providing empirical evidence from Islamic banking institutions in Indonesia over a ten-year period, highlighting the critical role of audit committee characteristics, particularly committee size and independence, in strengthening transparency and accountability practices aligned with SDG 16 (Peace, Justice and Strong Institutions).